A robust free-standing MoS2/poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) film for supercapacitor applications. (1st May 2017) - Ge, Yu; Jalili, Rouhollah; Wang, Caiyun; Zheng, Tian; Chao, Yunfeng; Wallace, Gordon G.
Graphical abstract: MoS2 /PEDOT:PSS hybrid film with high robustness and flexibility demonstrated an excellent capacitive performance in the form of an all-solid-state supercapacitor. Highlights: A robust free-standing MoS2 /PEDOT:PSS film has been prepared via a simple vacuum filtration method. MoS2 /PEDOT hybrid film displays remarkably improved mechanical robustness and flexibility. MoS2 /PEDOT electrode exhibits high volumetric capacitance and good cycling stability in aqueous electrolyte. Flexible MoS2 /PEDOT electrode can retain its capacitive performance over 1000 bending cycles in an all-solid-state supercapacitor. Abstract: Two-dimensional molybdenum disulfide (MoS2 ) is a promising energy storage material due to its high surface area and unique electronic structure. Free-standing flexible MoS2 -based electrode is of importance for use in flexible energy storage devices, whereas there are limited reports available. In this work we developed a robust hybrid film, MoS2 incorporated with highly conductive poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate). This free-standing film possesses excellent mechanical properties with a fracture strength of 18.0 MPa and a Young's modulus of 2.0 GPa. It can deliver a large volumetric capacitance of 141.4 F cm −3, a high volumetric energy density of 4.9 mWh cm −3, and a capacitance retention rate of 98.6% after 5000 charge/discharge cycles. This film has demonstrated its application in an all-solid-state bendable supercapacitor as well.